Determinants of wellbeing in adolescents and young adults ? a systematic review and case study - Bodzo, Panashe (Department of Public Health and Family Medicine, 2025)
Background: Adolescents and young people make up the greatest proportion of Sub-Saharan Africa (SSA). Understanding and improving their wellbeing should be considered a priority as it is associated with improved individual and societal wellbeing. Subjective wellbeing and psychological wellbeing are the two widely researched conceptualisations of wellbeing. Research on their determinants in adolescent populations has been concentrated in the global north. Interventions designed for this context are not likely to work in SSA due to the unique challenges in SSA. The aim of this study was to review the literature on the determinants of subjective and psychological wellbeing in SSA and organise these factors according to Bronfenbrenner's socio-ecological model. As of 2021, no systematic review had synthesised the literature on the determinants of wellbeing for adolescents and young people in SubSaharan Africa. Methods: This paper is a combination of a systematic review and a case study. The case study was included to triangulate the results of the systematic review in order to determine whether there are differences between the wellbeing of adolescents and young people in upper-middle-income countries and low to lower-middle-income countries in SSA. The review is based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement guidelines. A systematic search of the following databases was conducted: EBSCOhost, PubMed, Scopus, Google Scholar, OpenGrey and National Bureau of Economic Research (NBER). The search strategy included terminology on subjective and psychological wellbeing that is commonly used in the literature. The search strategy was guided by the literature review. For the case study, wave 5 data from the National Income Dynamic Study, which is a nationally representative longitudinal study conducted in South Africa was used. We ran a Probit regression with wellbeing as the predictor variable. Results: In total, 7701 results were returned, and 19 articles were eligible to be included in this review. Bronfenbrenner's socio-ecological model was used to classify and characterise the determinants of wellbeing for adolescents and young people identified in the systematic review and case study. The sample size for the case study was 6987, and age was restricted to 15 and 24. The mean age of this group was 19.31 (SD=2.84). 53% were females, and 49% resided in urban areas. 65% rated their wellbeing as average and above, and 17% were depressed, according to the CES-D-10 scale. Religion, intrinsic and extrinsic aspirations, household income and/or socio-economic status, trust in relatives and age were statistically significant (p<0.05) predictors of wellbeing among adolescents and young adults in SSA. Conclusion: This is the first study to systematically review and organise the determinants of wellbeing for adolescents and young adults in SSA. There is a need for multi-sectoral policies to aid in improving adolescent wellbeing. More research studies that use longitudinal data collected exclusively from adolescents and young people need to be conducted in SSA.